Inflammation and coronary microvascular disease: relationship, mechanism and treatment - Guo, Zehui; Yang, Zhihua; Song, Zhihui; Li, Zhenzhen; Xiao, Yang; Zhang, Yuhang; Wen, Tao; Pan, Guiyun; Xu, Haowei; Sheng, Xiaodi; Jiang, Guowang; Guo, Liping; et al. (Frontiers in Cardiovascular Medicine, 2024)
Coronary microvascular disease (CMVD) is common in patients with cardiovascular risk factors and is linked to an elevated risk of adverse cardiovascular events.Although modern medicine has made significant strides in researching CMVD, we still lack a comprehensive understanding of its pathophysiological mechanisms due to its complex and somewhat cryptic etiology. This greatly impedes the clinical diagnosis and treatment of CMVD. The primary pathological mechanisms of CMVD are structural abnormalities and /or dysfunction of coronary microvascular endothelial cells. The development of CMVD may also involve a variety of inflammatory factors through the endothelial cell injury pathway. This paper first reviews the correlation between the inflammatory response and CMVD, then summarizes the possible mechanisms of inflammatory response in CMVD, and finally categorizes the drugs used to treat CMVD based on their effect on the inflammatory response. We hope that this paper draws attention to CMVD and provides novel ideas for potential therapeutic strategies based on the inflammatory response.